1985
DOI: 10.2307/3899341
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Patterns of Cattle Grazing Behavior on Shortgrass Steppe

Abstract: Factors hzfluencing distribution of free-roaming cattle were studied on shortgrass steppe in northeastern Colorado. Spatial units selected for grazing were plant communities (soil-plant associations) and a stock-watering area. Regression models of grazing patterns were derived for growing-and dormant-season grazing patterns. Seasonal-grazing distribution was correlated with proximity to water (l/distance) and site-quality indicators. Internal validation of seasonal-grazing models indicated a good flt of predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
138
0
8

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(154 citation statements)
references
References 0 publications
7
138
0
8
Order By: Relevance
“…Costa et al (1990) has also shown slope to be the main factor. Flat areas are chosen by cattle as resting places (Peterson and Woolfolk 1955;Senft et al 1985;Jewell 2002;Gander et al 2003) and dung drop occurs mainly at the end of the rest. Low tree cover, few rock outcrops and high fodder potential are also linked to resting places.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Costa et al (1990) has also shown slope to be the main factor. Flat areas are chosen by cattle as resting places (Peterson and Woolfolk 1955;Senft et al 1985;Jewell 2002;Gander et al 2003) and dung drop occurs mainly at the end of the rest. Low tree cover, few rock outcrops and high fodder potential are also linked to resting places.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of grazing locations by cattle depends on herbage quality and quantity, water availability, relief, slope, elevation, aspect, natural and artificial barriers, herd social interactions, prior experience, and climate (Rice et al 1983). Cattle preferentially graze plant communities of high nutritive value (Osuji 1974;Anderson and Kothmann 1980;Roath and Krueger 1982) and this preference seems to partially control the distribution of cattle in a paddock (Van Rees and Hutson 1983;Senft et al 1985;Putman et al 1987). Pinchak et al (1991) concluded that the distance to water and physiographic complexity were the primary controls on cattle distribution, but that forage quality was an important predictor of cattle habitat use at finer grains.…”
Section: Patterns Of Cattle Habitat Usementioning
confidence: 99%
“…Herbivores may also be influenced in their choice of habitat by the microclimate offered by various habitats (Senft et al 1985). The extent to which animals are influenced by microclimate is likely to depend on their susceptibility to extreme conditions.…”
Section: Habitat Selectionmentioning
confidence: 99%
“…This finding fits well with the understandings that the relative preference for various species changes through the season (Grammon 1978;Holechek et al 1982). The abundance of seasonally preferred plant species have also been shown to influence the patterns of plant community use (Senft et al 1985). Also, the tendency of cattle to graze forest rather than grassland will increase as grasses mature toward the end of the growing season (Fitzgerald et al 1986).…”
Section: Plant Community and Patch Level Of Diet Selectionsupporting
confidence: 83%